Review of the genus Abiskomyia Edwards (Diptera: Chironomidae: Orthocladiinae), with description of new taxa from the Russian Far East and bordering territories - Makarchenko, Eugenyi A.; Makarchenko, Marina A. (Zootaxa, 2015)
A systematic review of the genus Abiskomyia Edwards, 1937 is presented based on materials from the Russian Far East and bordering territories. Three new species: A. korbokhon sp. nov., A. levanidovi sp. nov., A. rivalis sp. nov. and one subspecies A. virgo orientalis subsp. nov. are described and figured. Emended generic diagnoses and keys to determination of adult males, pupae and fourth instar larvae of all known species and subspecies of the Abiskomyia of the Palaearctic region are provided.